(untitled) (Proceedings of International Educators Conference, 2023)
Gathering information and knowledge has become an inevitable part of economic growth and development. The current information age presents many new challenges to achieve these much-needed goals. This paper attempts to highlight how information production through different means of information collection affects economic development.